PENGARUH HARGA, VARIAN PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN WISCO ICE (Survei Pada Konsumen Minuman Wisco Ice Di Surakarta) - Simanjuntak, Julianto; Pratiwi, Adcharina (Jurnal Bisnis dan Kewirausahaan, 2024)
The purpose of this study is to analyze the significance of the influence of price, product variants and promotions on purchasing decisions on Wisco Ice beverage consumers in Surakarta. This study uses a survey method, the types of data used are qualitative data and quantitative data, the data sources used are primary data and secondary data. The population in this study is Wisco Ice beverage consumers in Surakarta whose exact number is unknown. The number of samples studied was 100 people. The sample size was calculated using Leedy's formula. The sampling technique uses accidental sampling. Data collection methods used: questionnaires, observations and literature studies. Data analysis techniques used validity test, reliability test, classical assumption test, regression analysis. The results of the study concluded that price, product variants and promotions have a significant effect on purchasing decisions on Wisco Ice beverage consumers in Surakarta. The results of the determination coefficient obtained the result that the contribution of the influence given by price variables, product variants and promotions on the purchase decision of Wisco Ice beverage consumers in Surakarta was 74.6%, while the remaining 25.4% was influenced by other factors outside the variables studied, such as brand image, lifestyle, social media and product quality.